Residential Mobility, Self-Concept, and Positive Affect in Social Interactions - Oishi, Shigehiro (2007)
The present research examined (a) the link between personal history of residential mobility and the self-concept and (b) the implications of such a link for positive affect in social interactions. Study 1 showed that the personal self was more central to the self-definition of frequent movers than to that of nonmovers, whereas the collective self was more central to the self-definition of nonmovers than to that of frequent movers. Results from a laboratory and a 2-week event sampling study (Studies 2 and 3) demonstrated that frequent movers felt happier when an interaction partner accurately perceived their personal selves, whereas nonmovers felt happier when a partner accurately perceived their collective selves. These findings present the first direct evidence on how personal history of residential mobility is linked to important individual differences in the self and positive affect in social interactions.